2004
DOI: 10.1038/nature03034
|View full text |Cite
|
Sign up to set email alerts
|

Spatial scaling of microbial eukaryote diversity

Abstract: Patterns in the spatial distribution of organisms provide important information about mechanisms that regulate the diversity of life and the complexity of ecosystems. Although microorganisms may comprise much of the Earth's biodiversity and have critical roles in biogeochemistry and ecosystem functioning, little is known about their spatial diversification. Here we present quantitative estimates of microbial community turnover at local and regional scales using the largest spatially explicit microbial diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

42
485
7
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 560 publications
(542 citation statements)
references
References 24 publications
42
485
7
2
Order By: Relevance
“…The TAR measures the spatial turnover of community richness and allows the rate of community composition turnover (commonly referred to as z) to be calculated. According to Green et al 9 , z can be equivalently calculated from the increase of community richness with sampled area or from the decay of similarity in the community composition with increasing distance between sampling sites. Here the bacterial community composition of the soil samples was characterized by ARISA and the samples were sorted into OTUs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The TAR measures the spatial turnover of community richness and allows the rate of community composition turnover (commonly referred to as z) to be calculated. According to Green et al 9 , z can be equivalently calculated from the increase of community richness with sampled area or from the decay of similarity in the community composition with increasing distance between sampling sites. Here the bacterial community composition of the soil samples was characterized by ARISA and the samples were sorted into OTUs.…”
Section: Resultsmentioning
confidence: 99%
“…In microorganisms, phylogeographic studies have revealed that the genetic similarity within particular populations decreases with distance, which suggests a significant influence of dispersal limitation, leading to strong endemism 3 , and contradicts the hypothesis of microbial cosmopolitanism 8 . At the community level, biogeographical studies have indicated that diversity turnover is influenced both by geographical distance 9 and environmental heterogeneity (as classified by soil, vegetation and climatic characteristics) 10,11 . However, few in-depth studies have been carried out on the TAR of soil microorganisms, especially for soil bacteria, leading to a lack of concepts concerning the diversification processes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have detected variation in species composition in various habitats, both spatially (reviewed, for example, in Refs [35,[63][64][65]) and temporally (for example, Refs [66,67]). Spatio-temporal variation has been linked to variation in environmental conditions [35,68], even to the point at which environmental parameters can be predictive of species composition [55].…”
Section: Spatial and Temporal Variationmentioning
confidence: 99%